Locomotion rhythm makes power and speed - Bejan, A.; Gunes, U.; Almahmoud, H. (NATURE PORTFOLIO, 2023)
This article addresses two questions, why certain animals (frogs, breaststroke swimmers, hovering fliers, jellyfish) push rapidly against the surrounding fluid and then reach forward slowly, and whether this rhythm of propulsion is a manifestation of the universal phenomenon of design evolution in nature. Emphasis is on the distribution of time periods of locomotion in which, during the driving phase of cyclic movement (the motive stroke, phases 1 and 2, in alternating sequence with the dissipative stroke, phase 3), the work is generated (phase 1) and dissipated (phase 2). The relative lengths of the characteristic times t1 and t2 of the phases 1 and 2, are predicted. The relative duration of the proposed three phases of a cycle is the 'rhythm'. The analysis is based on a model of how the effective cross-sections of the stroking body parts impact the surrounding medium, water, or air, and the total power required to account for the kinetic energy losses during phases 2 and 3, which are due to drag forces posed by the surrounding medium. The body configuration (limbs' cross-sections) determines the limbs' velocities that maximize mean power, and the times t1 and t2 within the motive stroke. Emphasis is placed on the freedom to change the evolving design. Freedom is represented in two ways: the number of degrees of freedom in changing the dimensions of the model and its deformation in time, and the effect that evolutionary changes have on the access that the body has to its available space. Freedom to change the locomotion design leads to greater power and speed.
Keywords: CONSTRUCTAL THEORY; FLOW SYSTEMS; EVOLUTION; LAW; ANIMALS; DESIGN; TRADE; SHAPE; SIZE; Science & Technology - Other Topics